Assessment of entanglement risk to marine megafauna due to offshore renewable energy mooring systems. (September 2015) - Harnois, Violette; Smith, Helen C.M.; Benjamins, Steven; Johanning, Lars
Highlights: Comparison of the risk of entanglement of marine megafauna for ORE mooring systems. Parameters: tension characteristics, swept volume ratio and mooring line curvature. Case study with 6 mooring configurations commonly used for floating ORE devices. Catenary moorings and moorings using accessory buoys: higher risk of entanglement. The overall risk of entanglement is low. Abstract: This paper defines a methodology to compare different offshore renewable energy (ORE) mooring configurations in terms of the risk of entanglement they present to marine megafauna. Currently, the entanglement of large marine animals is not explicitly considered in environmental impact studies. Recommendations need to be developed, assessing the risk of entanglement of ORE mooring configurations at the beginning of their design process. Physical parameters of the mooring system affecting the relative risk of entanglement have been identified as tension characteristics, swept volume ratio and mooring line curvature. These have been investigated further through six different mooring configurations: catenary with chains only, catenary with chains and nylon ropes, catenary with chains and polyester ropes, taut, catenary with accessory buoys, taut with accessory buoys. Results indicate that the taut configuration has the lowest relative risk of entanglement, while the highest relative risk occurs with catenary moorings with chains and nylon ropes or with catenary moorings with accessory buoys. However, the absolute risk of entanglement is found to be low, regardless of the mooring configuration. This methodology can also be applied to other mooring configurations, arrays or power cables.